Determinants of well-being and welfare - Maciejasz-Świątkiewicz, Marta (Determinanty dobrostanu i dobrobytu, 2011)
People tend to think that money is the most important factor that make them happy. But not only do economic factors influence our happiness. There are lots of socio-demographic, ecological, cultural or psychological factors that determine our well-being and welfare. However, the problem with happiness is that the same actions can make one person happy but not another. This article presents in what ways all the aforementioned factors can determine our well-being, welfare and influence our happiness. Except for a pure educational use, this knowledge can be very useful for government while deciding about economic changes
Nauki o Finansach = Financial Sciences, 2011, Nr 1 (6), s. 171-178
Keywords: happiness; well-being; welfare; economy of happiness; behavioural economics